2014
DOI: 10.1111/jnc.12802
|View full text |Cite
|
Sign up to set email alerts
|

Primary glioblastoma cultures: can profiling of stem cell markers predict radiotherapy sensitivity?

Abstract: Human glioblastomas may be hierarchically organized. Within this hierarchy, glioblastoma-initiating cells have been proposed to be more resistant to radiochemotherapy and responsible for recurrence. Here, established stem cell markers and stem cell attributed characteristics such as self-renewal capacity and tumorigenicity have been profiled in primary glioblastoma cultures to predict radiosensitivity. Furthermore, the sensitivity to radiotherapy of different subpopulations within a single primary glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…To further explore the mechanisms of tunicamycin reducing GICs self-renewal, we investigated whether tunicamycin reduced the expression of genes regulating the self-renewal of glioma-initiating cell [24, 25]. Western blot assay and immunofluorescence assay showed that tunicamycin obviously reduced the expression of Sox2 (Figure 4A and 4B), a key gene sustaining self-renewal of normal and cancer stem cell [2628].…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the mechanisms of tunicamycin reducing GICs self-renewal, we investigated whether tunicamycin reduced the expression of genes regulating the self-renewal of glioma-initiating cell [24, 25]. Western blot assay and immunofluorescence assay showed that tunicamycin obviously reduced the expression of Sox2 (Figure 4A and 4B), a key gene sustaining self-renewal of normal and cancer stem cell [2628].…”
Section: Resultsmentioning
confidence: 99%
“…Although triple treatment did not further reduce CD133 + surface population compared to dual treatments, it reduced SOX2 expression a widely used marker for repopulating cells in context of radiation resistance [4142] as well as Nestin another stem cell marker in glioma progression [43–44]. This suggests that the treatment resistant population sensitive to NOTCH inhibitors is contained within the CD133, SOX2 and Nestin overlap expression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the treatment resistant population sensitive to NOTCH inhibitors is contained within the CD133, SOX2 and Nestin overlap expression. The phenotypic and functional identity of this population in vivo would be a key step forward in understanding glioma treatment resistance [45]. …”
Section: Discussionmentioning
confidence: 99%
“…20,21 CD44 protein marker expression correlates with molecular subtype of GBM 22 and positively associated with radioresistance of glioblastoma. 23 Data on the prognostic significance of CD44 in glioblastoma are controversial -it was suggested that enhanced CD44 expression is associated with poor survival rates in glioblastoma although this finding was not statistically significant; 24 lower levels of CD44 expression surprisingly correlated with lower survival for GBM patients. 25 Ki-67 is an established marker of cell proliferation, and Ki-67 index correlates with the clinical course of several cancer types.…”
Section: Introductionmentioning
confidence: 99%